2009
DOI: 10.1152/japplphysiol.00234.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quercetin supplementation is not ergogenic in untrained men

Abstract: Quercetin supplementation increases muscle oxidative capacity and endurance in mice, but its ergogenic effect in humans has not been established. Our study investigates the effects of short-duration chronic quercetin supplementation on muscle oxidative capacity; metabolic, perceptual, and neuromuscular determinants of performance in prolonged exercise; and cycling performance in untrained men. Using a double-blind, pretest-posttest control group design, 30 recreationally active, but not endurance-trained, youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 45 publications
4
47
1
Order By: Relevance
“…Nine studies were published in peerreviewed joumals. Four studies reported being fianded by a commercial interest (13,32,40,41), and two were funded by a federal agency (Table 1). Seven studies used a withinsubjects crossover experimental research design, with the other four using a randomized controlled trial with two independent groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were published in peerreviewed joumals. Four studies reported being fianded by a commercial interest (13,32,40,41), and two were funded by a federal agency (Table 1). Seven studies used a withinsubjects crossover experimental research design, with the other four using a randomized controlled trial with two independent groups.…”
Section: Resultsmentioning
confidence: 99%
“…In studies (21,47) that measured V02max or performance in the same subjects across multiple time points during the treatment (quercetin administration), standardized mean differences and variances were averaged across these time points. In studies that evaluated more than one experimental factor level, e.g., quercetin dosages of 1000 and 1400 mgd~' for independent subject groups compared with a single placebo group (40) or if the two outcomes of endurance exercise performance and V02max were measured in the same subjects (13,14,47), the ES was calculated for each comparison or outcome, respectively, and the mean was used as the study's ES. Meta-analyses were performed using a random-effects model that accounts for true interstudy variation in effects as well as for random error within each study (4).…”
Section: Study I Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively recent advent of polyphenol supplementation for exercise studies has necessarily resulted in a fairly narrow range of doses. Nonetheless, a variety of polyphenol sources has been tested (see Table 4) [3751]. On the one hand this is interesting, but on the other does not allow for much comparison as only quercetin testing has resulted in several studies.…”
Section: Polyphenol Supplementation and Exercisementioning
confidence: 99%
“…Of these, three peer-reviewed studies measured changes in V O 2max , and although mean changes indicated improvements ranging from 2.3 to 7.5 %, the changes were not all statistically significantly different from placebo. The duration of supplementation did not separate the statistical differences between studies and, although the doses differed, this also did not seem to affect the outcome: after 5 days of supplementation with 1,000 mg/day, V O 2max increased by 7.5 % [37], and after a similar duration of supplementation (7 days) resulted in a lower percentage improvement of 3.9 %, which was statistically significant [38]. The main difference between the two studies was a possible dose–response effect because the second study using half the dose (500 mg/day) of the first also revealed approximately half the percentage increase in V O 2max of that of the first study mentioned.…”
Section: Polyphenol Supplementation and Exercisementioning
confidence: 99%